Literacy skills, equality of educational opportunities and educational outcomes: an international comparison - Sonja Jovicic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper assesses the role of literacy skills as an equalizer in both educational outcomes and educational opportunities. First, by linking two surveys of adult skills for 11 OECD countries (PIAAC - Survey of Adult Skills (conducted in mid-90s) and IALS - International Adult Literacy Survey (conducted in 2011)), the relationship between performance (average literacy test scores) across countries and within-country skill inequality (dispersion in literacy test scores) is examined...
Keywords: I21; J62; J68; H52; 330